The modern technologies role in enhancing design determinants of safety and security factors in buildings: دور التقنيات الحديثة في تعزيز المحددات التصميمية لعوامل السلامة والأمان في المباني - Manar Abdul Hassan Raheem (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
The fire has devastating effects that lead to heavy material and human losses. Architectural design plays a role in reducing these losses by matching design to safety and security factors. Modern technology has played a great role in preventing, limiting, controlling and extinguishing the fire and thus reducing losses. The aim of the research is to highlight the design determinants of the building to prevent fire and the role of modern technologies in combating fire and preventing its spread, whether at the level of modern building materials used in building, finishing or furnishing the building or at the level of monitoring, The research deals with these data through three axes represented in the theoretical axis and deals with the concept of fire and its causes and the role of modern technologies in increasing the efficiency of origin in fire resistance. The second axis deals with analytical study of mix-use building and the statement of the most important design determinants used in the promotion of safety and safety factors to combat the fire and then review the most important findings and recommendations in the third axis. The researcher reached several results, most notably the ability of the architect and his freedom to use a wide range of materials for the construction and finishing of the building with fire-resistant materials developed by technology or by increasing the efficiency of traditional materials to resist fire by packaging or coating with fire retardants that contribute effectively to fire protection The research reached several recommendations, the most important of which is the need to keep pace with the architect of modern technology and work on applying it in its buildings to achieve the highest safety standards.